Determinan Pendapatan Driver Gojek di Kabupaten Badung - Kusuma, Umar Wira Hadi; Widanta, Anak Agung Bagus Putu (Peneliti.net, 2025)
Indonesia is currently entering a demographic bonus era, where the proportion of the productive-age population is larger than the non-productive age group. This phenomenon presents a significant opportunity for economic growth if the productive workforce can be effectively absorbed. Data from the Central Statistics Agency (BPS) shows an increase in labor absorption and a decline in unemployment rates from 2021 to 2023, partly driven by technological advancements, including online transportation services like Gojek. As a technology-based application company, Gojek has created extensive employment opportunities for the community, including in Badung Regency. However, the income of Gojek drivers is influenced by various factors, such as the duration of being on bid, activation of service features, age, and initial capital. This study uses a quantitative approach with a survey method involving 96 active Gojek drivers in Badung Regency. Data was collected through questionnaires and analyzed using moderation regression analysis with the help of SPSS version 27.The results show that the variables on bid, capital, and feature activation have a positive and significant impact on the income of Gojek drivers. The longer the on bid time, the greater the capital owned, and the more features activated, the higher the driver's income. However, the age variable does not show a significant effect on income. Feature activation also moderates the relationship between on bid, capital, and income, indicating that the use of application features can strengthen the influence of these variables on income.The implications of this research highlight the importance for Gojek drivers to maximize their on bid time, manage capital effectively, and optimize the use of application features to increase their income. Additionally, Gojek is advised to continue developing features that can help drivers improve efficiency and productivity. The government can also play a role by providing financial support and training to enhance the welfare of drivers.